The COVID-19 outbreak and public perceptions of sport events in Japan - Sato, S.; Oshimi, D.; Bizen, Y.; Saito, R. (Managing Sport and Leisure, 2022)
The pandemic of the COVID-19 has forced various sport organizations to postpone or cancel sport events. The current investigation provides a rapid analysis of public perceptions of (1) postponement and cancelation decisions made by sport organizations, and (2) whether the Tokyo Olympics 2020 should be held in July 2020. Data from Japanese citizens (n = 529) show that approximately 75% supported postponement decisions made by professional sport leagues. Surprisingly, only fewer than 50% supported the cancelation decision of the high school baseball tournament (i.e., Spring Koshien). Regarding the Tokyo Olympics, 35.2% disagreed with holding the games, which was almost identical to those who were in favour of holding it (35.3%). The government and decision-makers should recognize the potential biases in public opinions and prioritize the scientific evidence to protect the health of the community. (Note: The Tokyo Olympics and Paralympics 2020 was postponed after the completion of this study).